(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Human and animal health are increasingly affected by multidrug-resistant pathogens despite efforts to address the challenge. Research focus, shifted to microorganisms from extreme environments as possible sources of antibiotics and metabolites to halt this menace of resistance in pathogens. This paper explores the rich collection of metabolites produced by these microorganisms, their environment, and their applications. Given their intricate nature, these organisms may harbor mechanisms for producing novel metabolites and antibiotics to combat multidrug-resistant pathogens. We highlight recent advances in the isolation, screening, and characterization of antibiotic-producing extremophiles from their harsh terrestrial environments. Studying the diverse chemical scaffolds and mechanisms of action in these microbes can inform the development of effective antimicrobials. Furthermore, we discuss the challenges and prospects of harnessing the vast array of terrestrial microorganisms in extreme environments to combat antibiotic resistance.